Rancang Bangun Virtual Laboratorium Monopulse Secondary Surveillance Radar Berbasis Augmented Reality - Dian Anggraini Purwaningtyas; Johan Wahyudi; Feti Fatonah; Muh Wildan; Irvan Hanafi; Iga Ayu Mas Oka (Politeknik Penerbangan Indonesia Curug, 2022)
Monopulse Secondary Surveillance Radar (MSSR) is an important tool in monitoring air traffic, the complexity of radar equipment and the availability of radar equipment for practicum makes students and training participants less than optimal in learning radar, both theory and practice. Technological developments and increasing utilization of education are opportunities for updating learning. The purpose of this study is to find out the needs in learning radar with augmented reality by making MSSR prototypes, methods for manufacturing using the prototype method with the framework approach of the System Development Life Cycle, then for testing using black box testing, testing the function of the prototype and the results obtained. it is found that the function of the prototype is in accordance with the requirements document required in the implementation of radar education.